About neutron acceleration in uniform electromagnetic fields - Stepanovsky, Yu.P.; Zanimonskiy, Y.Y. (Вопросы атомной науки и техники, 2007)
It has been shown some time ago that a neutron undergoes some acceleration in uniform electromagnetic fields. We found an exact solution of Dirac wave equation for a neutron imbedded in a uniform electromagnetic field and our consideration of the problem doesn’t confirm the neutron acceleration. We provide the simple explanation why the statements about neutron acceleration are incorrect. Деякий час тому було показано, що нейтрон прискорюється в однорідних електромагнітних полях. Знайдено точне рішення хвильового рівняння Дірака для нейтрона, якій вміщено в однорідне електромагнітне поле, і наш аналіз питання не підтверджує прискорення нейтрона. Дано просте пояснення, чому твердження про прискорення нейтрона є хибними. Некоторое время назад было показано, что нейтрон ускоряется в однородных электромагнитных полях. Найдено точное решение волнового уравнения Дирака для нейтрона, помещенного в однородное электро-магнитное поле, и наш анализ вопроса не подтверждает ускорение нейтрона. Приведено простое объяснение, почему утверждения об ускорении нейтрона неверны.